Negative pressure wound therapy in elective stoma reversal surgery: results of a UK district general hospital pilot. Issue 3 (March 2020) - Shah, A.P.; Kurian, R.; Leung, E.
Summary: The role of negative pressure wound therapy in stoma reversal surgery remains unknown. To evaluate this, a retrospective, non-randomized, single-institution, pilot study was conducted. Surgeon preference determined type of wound closure and application of the single-brand negative wound pressure device. No patient in the intervention group suffered wound complications, but five of the thirty-six patients in the control group suffered surgical site infection-related complications. Primary closure and negative pressure wound therapy use decreases wound complications in stoma reversal surgery, thereby alleviating the wound-management burden in hospitals and in the community. This has cost-saving implications, but further studies are needed.